Análisis comparativo de habitabilidad entre una vivienda diseñada tradicionalmente y una vivienda con base en criterios sostenibles y resilientes enfocados en la optimización de recursos y uso de energías renovables - Córdova Rodríguez, Israel Abraham (2022)
The research focuses on the analysis of studies carried out between a traditionally used house located in the north of the city of Guayaquil, in the citadel orchids apple 1053 v10, whose main access roads are the 11A NO vehicular street that borders on its north with 1 Paseo 24A NO and to the south with Calle 24A NO, with a house based on criteria that seek to contribute to the solution of different common problems present in the projection of houses in the city of Guayaquil, which currently present problems with regarding the environment, sustainability, resilience and construction of spaces that allow quality habitability, since methods are used that are not very friendly with the environment, with the physical orientations of the building and even with the user. To achieve this goal, it is necessary to guide the design of homes based on sustainable and resilient criteria focused on reducing the use of air conditioning elements that emit pollutants into the environment, reusing natural elements and seeking to optimize thermal comfort within the home.